Estudio de prefactibilidad de una planta envasadora de lentejas (Lens culinaris) y comercialización en Lima metropolitana - Cruz Salazar, Catherine Pamela (2022)
The objective of this project is to the viability of a lens packaging plant and marketing in Metropolitan Lima. Chapter I refers to the problems that exist in the feeding of young people and adults; and the excessive consumption of single-use plastic bags. In addition, the technical, economic and social justifications of the project are raised. Likewise, to have the objectives and the hypothesis of the work to test the viability of the project. Chapter II covers the market study through the commercial definition and use of the product. In addition, to determine the geographical area of development, to find the potential demand and the demand for the project through the design and application of surveys in order to find the final demand for the project. Chapter III allows plant location, through the identification and analysis of location factors. For this project, the Factor Ranking method has been put into practice for both micro location and macro location. Chapter IV studies the size of the plant, through the relationship of the size of the plant with the market, productive resources, technology and break-even point. In this way, choose the best relationship to continue with the project. Chapter V exposes the engineering of the project according to the technical definition of the product, the existing technologies, production processes and the description of the process. Likewise, calculate the installed capacity, the number of machines and operators required; and plant layout. Chapter VI explains the organization and administration for the formation of the company, administrative staff requirements and the organization scheme. Chapter VII reviews the budget and evaluation of the project regarding long- and short-term investments; the cost of raw materials, labor and the indirect cost of manufacturing. In addition, it calculates the operating and financial budget. Chapter VIII studies the social evaluation of the project taking into account the social indicators and their interpretation.